Intellectual Property Creation of Japanese Companies in China and Thailand - Mayasuki Kondo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
In the age of globalization, Japanese companies are globalizing their operations. They have recently been increasing the number of overseas R&D centers in Asia, especially in China and Thailand. Using the United States patent and industrial design data, the paper finds the following points quantitatively. Japanese companies are increasing the number of patents and industrial designs created in the two countries. They used local talents from the beginning in China for both patents and industrial designs. In Thailand, they used local talents for industrial designs from the beginning, while Japanese expertise in Thailand was used for patents in the beginning. In any case, the role of Japanese in Japan is important. Compared with multi-national companies (MNCs) from other countries, the IP creation activities of Japanese companies are weak compared to their amount of foreign direct investment to China and Thailand.